A COMPARISON OF CNC LATHE MACHINE PROGRAMMING SIMULATION AND CNC LATHE MACHINE PRODUCTION RESULTS - Nugroho, Satrio Adi; Sena, Boni; Ujiburrahman, Ujiburrahman (Department of Mechanical Engineering Education, 2024)
This study compares the simulation results of a CNC lathe program with the actual production results of a CNC lathe. CNC lathes are used in the manufacturing of precision components for various industrial applications. Simulation of CNC lathe programs can provide an accurate estimate of the production output before the actual production process begins. In this study, we compared dimensional tolerance, geometric accuracy, and surface quality between simulated and actual results. The simulation method used is 2D modeling which involves the calculation of tool trajectories and cutting parameters inputted into the simulation panel. Actual production data was obtained from the measurement of components produced from the CNC lathe. A comparative analysis was conducted to evaluate the extent to which the simulation can predict the actual production results. The results show that, although the simulation can give a good picture, there is still a significant difference between the simulation results and actual production. The findings have practical implications in improving efficiency and accuracy in the planning and production process using CNC lathes.